Comparison of Culture and Rapid Enzyme Immunoassay for the Detection of Group B Streptococcus in High-Risk Pregnancies. Issue 3 (1994) - Dinsmoor, Mara J.; Dalton, Harry P.; Peng, Thomas C. C.; Christmas, James T.; Sayahtaheri-Altaie, Sousan; Harvey, Kevin; VanDorsten, J. Peter
Abstract : Objective: The purpose of this study was to evaluate the Equate Strep B® test for clinical use in patients at high risk for complications from group B streptococcus (GBS) disease. Methods: Vaginoperineal swabs were obtained from patients with preterm premature rupture of the membranes and/or preterm labor and semiquantitative GBS cultures and Equate® assay were performed. Results: From May 14, 1990, to April 30, 1992, 650 patients were enrolled; 626 had both culture and Equate® results available, of whom 24% were colonized with GBS. The sensitivity, specificity, positive predictive value, and negative predictive value of the rapid assay were 28%, 84%, 35%, and 79%, respectively. Although the prevalence of GBS was higher in patients with ruptured membranes compared with those with intact membranes, rupture of membranes did not affect test sensitivity or specificity. Conclusions: We conclude that the Equate® rapid assay is not a sensitive method of GBS detection in high-risk patients.